The Palgrave Handbook of Political Economy (Palgrave Macmillan UK, 2018)
This book is a major contribution to the study of political economy. With chapters ranging from the origins of political economy to its most exciting research fields, this handbook provides a reassessment of political economy as it stands today, whilst boldly gesturing to where it might head in the future. This handbook transcends the received dichotomy between political economy as an application of rational choice theory or as the study of the causes of societies' material welfare, outlining a broader field of study that encompasses those traditions. This book will be essential reading for academics, researchers, students, and anyone looking for a comprehensive reassessment of political economy. .